2012
DOI: 10.4261/1305-3825.dir.5790-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid spect-CT for characterization of isolated vertebral lesions seen on bone scintigraphy: comparison with planar scintigraphy, spect and CT

Abstract: RESULTSAmong the 108 lesions, 49 were indeterminate on planar scintigraphy, 16 on SPECT, and one each on SPECT-CT and CT. SPECT-CT was superior to both planar scintigraphy (P < 0.001) and SPECT alone (P = 0.014), but not to CT (P = 0.302). CT was superior to planar scintigraphy (P < 0.001) but only slightly superior to SPECT (P = 0.063). SPECT-CT correctly characterized 96% of the indeterminate lesions observed by planar scintigraphy. SPECT-CT had an impact on the clinical management of 60.6% patients compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…SPECT/CT provides a unique opportunity to correlate the scintigraphic findings with their morphologic counterpart. The current evidence shows that SPECT/CT reduces the number of equivocal findings on the planar scan, increases the diagnostic confidence, and improves accuracy and specificity [41][42][43] (Fig. 26).…”
Section: Figure 10mentioning
confidence: 85%
“…SPECT/CT provides a unique opportunity to correlate the scintigraphic findings with their morphologic counterpart. The current evidence shows that SPECT/CT reduces the number of equivocal findings on the planar scan, increases the diagnostic confidence, and improves accuracy and specificity [41][42][43] (Fig. 26).…”
Section: Figure 10mentioning
confidence: 85%
“…For characterizing vertebral lesion 99m Tc-MDP SPECT/CT is superior to planar bone scan and SPECT alone, but not to CT alone [4]. SPECT/CT also significantly reduces number of spinal lesion judged equivocal in SPECT alone [5].…”
Section: Casementioning
confidence: 95%
“…Some authors observed poorer detection of metastases particularly in the pelvis, spine and sacrum with the planar scintigraphy 38 . The greatest benefit of SPECT/CT is reported, however, for these localizations 24 . The authors drew attention to the lower availability and higher cost of PET/CT versus SPECT/CT for a routine check-up 34 .…”
Section: Comparison With Hybrid Systems Using Petmentioning
confidence: 99%
“…This resulted in a change in treatment of patients in 61% compared to a planar scintigraphy and in 18% compared to SPECT (ref. 24 ). Concerning the examination of patients with back pain, there was a threefold improvement of the characteristics of indeterminate lesions by SPECT/CT versus SPECT (ref.…”
Section: Detection Of Bone Metastasesmentioning
confidence: 99%